1975
DOI: 10.1084/jem.141.2.502
|View full text |Cite
|
Sign up to set email alerts
|

H-2 compatibility is required for T-cell-mediated lysis of target cells infected with lymphocytic choriomeningitis virus.

Abstract: Maximal cell-mediated lysis of targets infected with lymphocytic choriomeningitis virus occurs only within a H-2 compatible system. Syngeneic immune spleen cells are at least 100 times as effective as are allogeneic lymphocytes. Reciprocal restriction of cytotoxic T-cell activity has been shown to operative between H-2k, H-2d, and H-2b. Experiments with cogenic mice have localized the effect to the H-2 gene complex. Furthermore, the observation that lymphocytes from H-2a mice cause high specific 51Cr release f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
98
1

Year Published

1975
1975
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 283 publications
(101 citation statements)
references
References 12 publications
2
98
1
Order By: Relevance
“…This interest stems largely from the observation that cytotoxic thymus-derived (T) lymphocytes generated in mice in response to viral infection will lyse virus-infected H-2-compatible, but not H-2 incompatible, target cells in the 5lCr release cytotoxicity assay. This observation, initially reported with lymphocytic choriomeningitis virus (1), has been confirmed with vaccinia (2), ectromelia (3), Sendai (4), and 1; riend leukemia (5) viruses. Two general explanations have been proposed to account for the requirement of H-2 compatibility between lymphocytes and virus-infected target cells.…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…This interest stems largely from the observation that cytotoxic thymus-derived (T) lymphocytes generated in mice in response to viral infection will lyse virus-infected H-2-compatible, but not H-2 incompatible, target cells in the 5lCr release cytotoxicity assay. This observation, initially reported with lymphocytic choriomeningitis virus (1), has been confirmed with vaccinia (2), ectromelia (3), Sendai (4), and 1; riend leukemia (5) viruses. Two general explanations have been proposed to account for the requirement of H-2 compatibility between lymphocytes and virus-infected target cells.…”
mentioning
confidence: 60%
“…The alternative concept is that T cells recognize either normal or modified H-2 antigens and that both viral and H-2 specific antigenic recognition are required for cell lysis. This concept has been referred to as the "physiological interaction" or "dual recognition" hypothesis (1,6,9). Published studies have indicated that lymphocytic choriomeningitis, ectromelia, and Sendai virusinfected target cells can be distinguished by cytotoxic T lymphocytes from appropriately immunized syngeneic mice (4).…”
mentioning
confidence: 99%
“…Since the recent independent discoveries that viruses (8)(9)(10)(11)(12), and chemicals Tables I and II, however, semiallogeneic or allogeneic CML reactions with unmodified stimulating cells generated effectors which lysed to a variable extent (8 .1-23 .1%) any TNP-modified target spleen cell . This observation illustrates the importance of using only syngeneic mixtures of responder and stimulating cells in the sensitization phase of the CML .…”
Section: Discussionmentioning
confidence: 99%
“…Macrophages are members of the reticuloendothelial system and are probably the first cells to take up free virus from the circulation. Although it is not known as yet how and if cytotoxic T cells (24)(25)(26)(27)(28) play any direct role in controlling virus growth and/or spreading, interaction (cytolytic or noncytolytic in vivo) between T cells and infected macrophages are probably important for this function (reviewed in 29). These cells may thus represent biologically relevant targets.…”
Section: Discussionmentioning
confidence: 99%